Hydrological monitoring in open PIT mining areas using geodatabase attribute in Geographic Information Systems (GIS). Issue 4 (April 2020) - Isniarno, N F; Aziz, G; Iswandaru, I
Abstract: In open mining systems, the most important problem in mining production activities is surface water management, where surface water management is an integrated water management activity with the aim of minimizing the negative influence of surface water which consists of mine drainage methods, mine drainage, sediment separation and control. Geographic Information Systems (GIS) can be used for hydrological analysis using spatial data, especially in calculating runoff discharges from surface water. The method used in calculating runoff discharge is in the form of daily rainfall data. This rainfall data can show the influence of the catchment area which is useful for knowing precisely and accurately the runoff water discharge. Geographic Information Systems (GIS) are used to calculate variables in rational formula equations by overlay analysis. Information about digital-based hydrological conditions is very useful as a means of decision making and policies undertaken in monitoring hydrological conditions in open mines. By using a geographic information system (GIS) with a geodatabase attribute, it can be used to view general conditions in a mining area in monitoring hydrological conditions. So it is very appropriate to be used as hydrological monitoring in the mining area in making decisions that are fast, precise and accurate. Apart from that the geodatabase attribute can see the actual conditions of a mining area.